2016
DOI: 10.1002/jnr.23923
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection by central nervous system remyelination: Molecular, cellular, and functional considerations

Abstract: Oligodendrocytes and their myelin sheaths play an intricate role in axonal health and function. The prevalence of white matter pathology in a wide variety of central nervous system disorders has gained attention in recent years. Remyelination has therefore become a major target of therapeutic research, with the aim of protecting axons from further damage. The axon-myelin unit is elaborate, and demyelination causes profound changes in axonal molecular domains, signal transmission, and metabolism. Remyelination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 107 publications
(108 reference statements)
0
22
1
Order By: Relevance
“…Microglial activation with enhanced release of inflammatory mediators is known to impair myelination in different models of WM injury 24 . Here, we found the number of cells positive for the general marker Iba-1 and the phagocytosis marker CD68 were remarkably elevated in BCAS mice, reached the peak on the 10th day after BCAS and then sustained the status of highly activated (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Microglial activation with enhanced release of inflammatory mediators is known to impair myelination in different models of WM injury 24 . Here, we found the number of cells positive for the general marker Iba-1 and the phagocytosis marker CD68 were remarkably elevated in BCAS mice, reached the peak on the 10th day after BCAS and then sustained the status of highly activated (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that the neuroinflammation response can contribute to the pathogenesis of ischemic stroke 2, 4, 8, 21 . M2 type microglia have been reported to be an essential part of the regenerative response in CNS demyelinating diseases by promoting oligodendrocyte differentiation 22 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Myelin depletion is a major pathological event in inflammatory diseases, vascular and traumatic lesions of the central nervous system (CNS), and a major cause of consequent neurodegeneration and chronic disabilities in both infants and adults (Verden & Macklin, ). Oligodendrocyte precursor cells (OPCs) are the cells responsible for myelin formation during development, and for myelin turnover and repair during the adult life, thanks to their ability to differentiate into myelinating oligodendrocytes (OLs) (Alizadeh, Dyck, & Karimi‐Abdolrezaee, ).…”
Section: Introductionmentioning
confidence: 99%